2004
DOI: 10.1002/pssb.200304139
|View full text |Cite
|
Sign up to set email alerts
|

Growth by MBE and characterization of metastable group II sulphides

Abstract: Many group II sulphides semiconductors have the rocksalt structure as their stable crystal structure. In the case of MgS and MnS it has been demonstrated that these compounds can be grown in the metastable zinc blende structure. Recently, at Heriot-Watt we have shown that a simple MBE growth procedure can be used to increase the thickness of these metastable layers to over 130 nm. In this paper, we summarise some of the results we have obtained and describe some of the structures which we have grown using thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Previously, we observed the loss of the ZB crystal structure and assumed that transformation had occurred directly to the stable phase, NaCl [7,8,13]. At present, however, we have no direct evidence for the formation of this phase, rather than an orthorhombic metastable structure.…”
Section: Transformation Of Zb To Rocksaltmentioning
confidence: 71%
See 1 more Smart Citation
“…Previously, we observed the loss of the ZB crystal structure and assumed that transformation had occurred directly to the stable phase, NaCl [7,8,13]. At present, however, we have no direct evidence for the formation of this phase, rather than an orthorhombic metastable structure.…”
Section: Transformation Of Zb To Rocksaltmentioning
confidence: 71%
“…Aspects of this work have been reviewed recently [13], with emphasis on the growth method and wide range of structures developed incorporating MgS or MnS. Here, we review the structural properties of the metastable sulphides.…”
Section: Introductionmentioning
confidence: 99%
“…This requires a value for the lattice parameter of CrS, a CrS , in order to calculate the Cr mole fraction, x, in the Mn 1-x Cr x S layers. Initially a value of 5.806 Å was used for a CrS based on the previous estimates made at Heriot-Watt [4]. Figure 1 shows the 004 XRI and simulated data for the structure grown with T Cr = 1010 °C (Sample 1).…”
Section: Growth Proceduresmentioning
confidence: 99%
“…Preliminary calculations were carried out at Heriot-Watt using published atomic radii to calculate the lattice parameters of the first row transition metal sulphides and then taking into consideration the known lattice parameter of MnS. This indicated that the lattice parameter could be as large as 5.806 Å [4]. However, ab initio calculations carried out by I. Galanakis et al [5] have determined the lattice parameter of CrS to be 5.04 Å, while H. Shoren et al [6] calculated it as 5.309 Å.…”
Section: Introductionmentioning
confidence: 99%
“…The films are, however, usually polycrystalline and exhibit a mixture of different crystallographic phases. We have shown earlier that MnS can be grown in the metastable zinc blende (ZB) phase with ZnSe cladding layers [6,7]. Bulk ZB MnS is a fcc type III antiferromagnet, but the effect of reducing the layer thickness and the presence of the interfaces on the magnetic phase transition are unknown.…”
mentioning
confidence: 98%